Plant nutrients in a degraded soil treated with water treatment sludge and cultivated with grasses and leguminous plants - Teixeira, Sandra Tereza; José de Melo, Wanderley; Tomé Silva, Érica (Elsevier, 2007)
The objective of this work was to evaluate rates for applications of water treatment sludge (WTS) as a nutrient source for grasses and leguminous plants cropped in a soil degraded by tin mining in the Amazon Region (Natural Forest of Jamari, Rondonia State, Brazil). The treatments consisted of three rates of nitrogen supplied by WTS (100, 150 and 200 mg kg -1 soil), five combinations of plants, two controls (absolute control, without fertilization; and chemical control, soil+lime+chemical fertilizers). WTS modified the contents of macro and micronutrients in the degraded soil, but it was not, as used in the present study, sufficient for the rehabilitation of the degraded area. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Amazon Basin; Mining; Residue; Soil fertility; Soil rehabilitation; Nitrogen compounds; Nutrients; Plants (botany); Sewage; Soils; Water treatment sludge (WTS); Water treatment; grass; legume; mining; recycling; sludge; soil amendment; soil degradation; soil fertility; soil remediation; Amazonia; Brazil; Jamari National Forest; Rondonia; South America; Fabaceae; Poaceae